2011
DOI: 10.3122/jabfm.2011.03.110066
|View full text |Cite
|
Sign up to set email alerts
|

Response: Re: Trimethoprim-sulfamethoxazole or Clindamycin for Community-Associated MRSA (CA-MRSA) Skin Infections

Abstract: To the Editor: We thank Khawcharoenporn for his comments regarding our recent study involving patients with CA-MRSA skin and soft tissue infections (SSTIs). 1 This study includes a subgroup analysis of patients who received incision and drainage (I&D) alone versus I&D plus antibiotics (94% received trimethoprim-sulfamethoxazole or clindamycin). Retrospective, observational studies like ours are potentially subject to selection bias; however, a comparison of baseline characteristics revealed no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A recent national survey of 207 board-certified emergency department physicians found that 80% would sometimes or always prescribe antibiotics in addition to I&D for simple abscesses; 81% of those who endorsed adjunctive antibiotics preferred antibiotics with MRSA activity. 6 Christopher R. Frei College of Pharmacy, Pharmacotherapy Division University of Texas Austin, TX…”
mentioning
confidence: 99%
“…A recent national survey of 207 board-certified emergency department physicians found that 80% would sometimes or always prescribe antibiotics in addition to I&D for simple abscesses; 81% of those who endorsed adjunctive antibiotics preferred antibiotics with MRSA activity. 6 Christopher R. Frei College of Pharmacy, Pharmacotherapy Division University of Texas Austin, TX…”
mentioning
confidence: 99%